2002
DOI: 10.1128/jcm.40.6.1994-2001.2002
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of Bordetella pertussis Based on Surface Protein Genes

Abstract: Despite more than 50 years of vaccination, Bordetella pertussis has remained endemic in The Netherlands, causing epidemic outbreaks every 3 to 5 years. Strain variation may play a role in the persistence of B. pertussis and was studied by sequencing 15 genes coding for surface proteins, including genes for all five components of acellular pertussis vaccines: pertussis toxin (Ptx), pertactin (Prn), filamentous hemagglutinin, and fimbriae (Fim2 and Fim3). A low level of allelic variation was observed, confirming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
137
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 37 publications
2
137
1
2
Order By: Relevance
“…54 %) with those of the Japanese strains. Surface-protein genes are subject to greater selective pressure and change more rapidly than housekeeping genes such as tuf, particularly in pathogenic bacteria exposed to immune responses (van Loo et al, 2002). The inconsistencies between the slp tree and those derived from 16S rRNA and tuf genes indicated that the slp gene may not provide an accurate picture of the phylogenetic relationships of these organisms and may be subject to lateral transfer.…”
mentioning
confidence: 89%
“…54 %) with those of the Japanese strains. Surface-protein genes are subject to greater selective pressure and change more rapidly than housekeeping genes such as tuf, particularly in pathogenic bacteria exposed to immune responses (van Loo et al, 2002). The inconsistencies between the slp tree and those derived from 16S rRNA and tuf genes indicated that the slp gene may not provide an accurate picture of the phylogenetic relationships of these organisms and may be subject to lateral transfer.…”
mentioning
confidence: 89%
“…The identification of gene polymorphism in bacteria by nucleotide sequence analysis of genes encoding antigenic surface proteins jointly with genes encoding housekeeping proteins has been proven useful in the surveillance of pathogenic bacteria (Byun et al, 1999;Maiden et al, 1998;van Loo et al, 2002;Kotetishvili et al, 2003). Particularly multilocus sequence typing (MLST) schemes where data can be stored, analysed and queried through a central web server have permitted local and global epidemiology studies of several infectious agents (Chan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This method was first described by Maiden and colleagues [34] as a tool for strain discrimination of Neisseria meningitis strains and has since been used extensively to distinguish strains of pathogenic bacteria [18,52,62]. MLST is based on direct nucleotide sequencing of a target locus, to which a unique and arbitrary allele number is assigned.…”
Section: Introductionmentioning
confidence: 99%